(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This review examines the concept of invisible replacement risk, referring to the gradual and often insidious implications of artificial intelligence (AI) for job security, which do not necessarily manifest as immediate layoffs. Unlike traditional forms of automation that result in clearly identifiable job losses, invisible replacement risk captures the progressive reallocation of job tasks, heightened employee anxiety, shifting workplace dynamics, and the emergence of new incentive-related challenges. This paper synthesizes key findings from the literature, elucidates the underlying mechanisms driving these transformations, and explores the evolving role of human labor in relation to AI systems. Furthermore, it critically assesses the associated policy and ethical implications. The review concludes by emphasizing the necessity of adaptive strategies and inclusive policy frameworks to effectively support workers within an increasingly AI-augmented labor market.